Cortical Reorganization in Patients Recovered from Bell’s Palsy: An Orofacial and Finger Movements Task-State fMRI Study - Jaeyoun Lee; Jun Yang; Chuanfu Li; Aihong Yuan; Hongli Wu; Anqin Wang; Qiuju Xue; Tao Wang; Linying Wang; Ting Gao (Neural Plasticity)
Objective. To explore cortical reorganization of patients recovered from Bell’s palsy (BP) by task-state functional magnetic resonance imaging (fMRI) during finger and orofacial movements and provide more evidence for acupuncture clinical treatment of BP. Methods. We collected 17 BP patients with complete clinical recovery (BP group) and 20 healthy volunteers (control group) accepted the task-state fMRI scans with lip pursing movements and finger movements, respectively. Results. It was found that there were significant differences of brain functional status between the two groups. Conclusions. The results showed that there was cortical reorganization in the brain of patients recovered from BP after acupuncture treatment, which also suggested the relationship between the hand motor areas and facial motor areas of BP patients.